Advancing health equity through CTSA programs: Opportunities for interaction between health equity, dissemination and implementation, and translational science. Issue 3 (28th June 2020) - Yousefi Nooraie, Reza; Kwan, Bethany M.; Cohn, Elizabeth; AuYoung, Mona; Clarke Roberts, Megan; Adsul, Prajakta; Shelton, Rachel C.
Abstract: Dissemination and implementation (D&I) science is dedicated to studying how to effectively translate and apply research in real-world contexts. There has been increasing interest in health equity within the D&I field to ensure the equitable implementation of evidence-based programs/practices across a range of diverse populations and settings. At the same time, health equity researchers recognize the potential of D&I science to promote the more widespread dissemination, implementation, and sustainment of evidence-based interventions to address health inequities. The National Center for Accelerating Clinical and Translational Science Clinical and Translational Science Award (CTSA) Program has been a champion for community engagement and translational scholarship in its mission to improve individual and population health. The overall CTSA infrastructure and resources within and among CTSA hubs are well-equipped to facilitate a health equity focus to D&I across the phases of translational research. This paper proposes a framework that demonstrates the interaction and opportunities between health equity and D&I science and highlights how CTSAs can support and facilitate wider efforts in translational research with a focus on equitable D&I.